Uji Tinggi Muka Air Tanah Gambut dan Pemberian Abu Tandan Kosong Kelapa Sawit (ATKKS) terhadap Pertumbuhan dan Produksi Tanaman Kedelai (Glycine max L.) - Irawati, Irawati; Wawan, Wawan; Ramahdini, Isna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to determine the best interaction of high peat groundwater level and giving oil palm empty bunches ash to the growth and production of soybean plants, this research has been conducted in the green house of Agriculture Experimrntal Station Faculty of Agriculture University Riau, from November 2017 untill February 2018. this research was conducted experimentally by using Completely Randomized Design (RAL) which is consist 2 factors. First factor is the groundwater level (T), 30 cm below the foil surface, 40 cm below the foil surface. Second factor is oil palm empty bunches ash (A) 2,5 ton.Ha-1, 5 ton.Ha-1. The data obtained were analyzed  statistically using analysis of  variance with Duncan New Multiple Range Test (DNMRT) at 5%. The result showed the interaction of giving oil palm empty bunches ash and groundwater level, significantly affected pH, plant height, effective percentage of root nodules, harvest age, number of planting pods, dry seed weight, weight of 100 seeds, percentage of pods, and root length. And had no significant effect to other parameters. The combination of giving oil palm empty bunches ash 5 ton.Ha-1 and 30 cm below the foil surface  gave the best results on parameters of plant height (92,96 cm), number of pods per plant (79,16 pods), dry seed weight of crop (12,07 g), percentage of pods (71,33%) and weight of 100 seeds (9, 44 g).Keywords: Groundwater level, oil palm empty bunches (ATKKS), peat soil, soybean (Glycine max L.)